2023
DOI: 10.1002/fsn3.3353
|View full text |Cite
|
Sign up to set email alerts
|

Edible film based on corn zein containing dill extract and essential oil/β‐cyclodextrin inclusion complex: Shelf life enhancement of common carp fillet

Abstract: Due to its high nutritional value, abundance, growth rate, and pleasant taste, the common carp (Cyprinus carpio) is known as one of the main edible freshwater fish species. High pH value, polyunsaturated fatty acids, and nonprotein nitrogen (NPN) compounds followed by fast microbial growth, oxidation, and autolytic reactions have decreased the shelf life of this desirable product (Moosavi-Nasab et al., 2016). Active edible films and coatings with natural origin are the new approach for the shelf life enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…They concluded that this effect can be related to the antibacterial effects of the designated coating in the studied chicken meat during storage time (Barkhordari & Bazargani‐Gilani, 2021 ). Zolfaghari et al ( 2023 ) observed the significant ( p ≤ .05) antibacterial activity of the zein edible film containing encapsulated dill essential oil and extract in the refrigerated common carp fillets. They reported that the designated zein edible film could significantly ( p ≤ .05) control the pH changes of the studied samples compared to the unwrapped fillets during 12 days of the storage period.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They concluded that this effect can be related to the antibacterial effects of the designated coating in the studied chicken meat during storage time (Barkhordari & Bazargani‐Gilani, 2021 ). Zolfaghari et al ( 2023 ) observed the significant ( p ≤ .05) antibacterial activity of the zein edible film containing encapsulated dill essential oil and extract in the refrigerated common carp fillets. They reported that the designated zein edible film could significantly ( p ≤ .05) control the pH changes of the studied samples compared to the unwrapped fillets during 12 days of the storage period.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, potent antimicrobial effects of Ag nanoparticles caused the low bacterial population, followed by the low TVB‐N value in the cold‐stored turkey breast meat. Zolfaghari et al ( 2023 ) designed an edible film based on corn zein containing encapsulated dill essential oil for the shelf‐life enhancement of the common carp fillets under refrigeration conditions. They concluded that the produced activated zein film had significant ( p ≤ .05) antibacterial activity and therefore could prevent the increase in the TVB‐N value in the common carp fillets during storage period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations